The Influence Of Reactant Ratio (Eupcalyptus Lignin – Sodium Bisulfite) And Initial Ph Towards Characteristcs Of Sodium Lignosulfonate - Gustini Syahbirin; ABDUL Aziz Darwis; Ani Suryani; Wasrin Syafii (Jurnal Teknologi Industri Pertanian, 2009)
Eucalyptus lignin was isolated from kraft black liquor through by acidification using H2SO4. Sulfonation of eucalyptus lignin produced sodium lignosulfonate (SLS) which can be used as dispersants, and emulsifier. In this research, sulfonation was carried out towards lignin with mass ratio of eucalyptus lignin-NaHSO3 (b/b) of 1:0.4, 1:0.5, and 1:0.6, and initial pH of 5, 6, 7, 8. Studies on the effect of various ratio of eucalyptus lignin versus NaHSO3 (1 based on w/w) and initial pH of 5,6,and 7 for the sulfonation reaction showed an  increasing yield and improved purity of SLS obtained.  However, no significant result was observed on the application of initial pH  7 and 8 toward increasing of SLS yield and purity.  The highest SLS  yield of 83.8% with  purity of 82.9% was obtained under condition of initial pH at 7 and the mass ratio of eupcayptus lignin over NaHSO3 was 1:0.5.  The resulted SLS was light brown, water soluble, with  pH level between 6.3 and 7.24, and released sulfur-like odor.Key words: lignin, kraft black liquor,  sodium lignosulfonate.